Teaching Writing Through Canva Application at MTS Al-Islamiyah Ciledug - Qondila Paulia (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2021)
This study aims to determine how effective the use of Canva application media is in teaching writing. This research was conducted in July-August at Mts Al-Islamiyah, Ciledug. Researchers used quantitative methods with pre-experimental methods by applying pre-test and post-test as instruments in collecting data. Researchers used one class in class IX-1 MTs Al-Islamiyah Ciledug as the population. The method in this study using the rendom sampling technique used in class IX-1. The mean score on the post test was 70.83 and the pre-test was 64.73. It also shows that the Tcal value (9,585) is higher than the Ttable (2.021), at the 5% significance level. If the result t-test is higher than t-table, the alternative hypothesis (Ha) is accepted, and (H0) is rejected. Based on the results of the t-test calculation above, because the positive hypothesis (Ha) is accepted, it can be concluded that the Canva Application is an effective use of media in teaching writing skills.